2021
DOI: 10.1186/s13287-021-02153-8
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell-derived exosomes: therapeutic opportunities and challenges for spinal cord injury

Abstract: Spinal cord injury (SCI) often leads to serious motor and sensory dysfunction of the limbs below the injured segment. SCI not only results in physical and psychological harm to patients but can also cause a huge economic burden on their families and society. As there is no effective treatment method, the prevention, treatment, and rehabilitation of patients with SCI have become urgent problems to be solved. In recent years, mesenchymal stem cells (MSCs) have attracted more attention in the treatment of SCI. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
110
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(110 citation statements)
references
References 170 publications
0
110
0
Order By: Relevance
“…Previous studies showed that EVs promote functional recovery in mice post-injury, 20,32,33 and in this study, we investigated whether MEVs have greater beneficial effects than EVs. Functional behavioral evaluations were conducted at indicated time points (Figure 2A).…”
Section: Administration Of Mevs Promotes Better Functional Behavioral Recovery After Sci In Micementioning
confidence: 94%
See 1 more Smart Citation
“…Previous studies showed that EVs promote functional recovery in mice post-injury, 20,32,33 and in this study, we investigated whether MEVs have greater beneficial effects than EVs. Functional behavioral evaluations were conducted at indicated time points (Figure 2A).…”
Section: Administration Of Mevs Promotes Better Functional Behavioral Recovery After Sci In Micementioning
confidence: 94%
“…18,19 It has also been shown that these nanosized MSCs-derived extracellular vesicles can successfully cross the BBB and promote functional recovery after SCI. 20 Preconditioning, by cytokines, drugs, hypoxic conditions, or physical factors, which improves transplantation efficacy, is an important way of improving the biological function of MSCs and enhancing paracrine effects. 21 The hormone melatonin (MT), which was first isolated from the pineal gland and is widely distributed throughout the body, is a free radical scavenger and a broad-spectrum antioxidant.…”
Section: Introductionmentioning
confidence: 99%
“…Spinal cord injury (SCI) is one of the most serious complications of spinal fracture, which mostly results in severe sensory and motor dysfunction, even paraplegia [1,2]. Recent studies have explained that the exosomes (Exo) secreted from mesenchymal stem cells (MSCs) may take the central role behind their potential therapeutic effect on SCI [3,4]. Moreover, apart from Exo's penetration across the blood-brain/spinal cord barrier depending on their small size, they also manifest a promising advantage of homing to injury sites of the central nervous system driven by inflammation [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the extensive research on cell transplantation strategies for SCI management, the mechanism has still to be clarified how transplant cells provide an interaction with the host cells, either directly or indirectly, thereby promoting repair and mediating functional improvement. In addition, stem cell therapy is limited by tumorigenicity, low survival rate, and immune rejection, such that the clinical applications of stem cell cells are frequently restricted by a variety of factors (Liu et al, 2021). Additionally, glial scar formation prevents the integration, differentiation, and axon regeneration of transplanted stem cells in the diseased area, resulting in permanent functional defects.…”
Section: Introductionmentioning
confidence: 99%